The 2014 European electoral manifestos a preliminary analysis of the main competition dimensions - Fernandes, J. M.; Santana Pereira, J. (Relações Internacionais, 2018)
The European project has enjoyed considerable support from both elite and masses in Portugal. Since the country joined the EEC in 1986, the main political parties have been strong supporters of the Europe project. In recent years, however, this has been undermined by both political and economic crises. In this paper, we produce a preliminary analysis of the competition dimensions in the forthcoming 2014 European elections. We make an empirical analysis of the position held by the five most important Portuguese political parties in relation to European integration, the Euro, debt renegotiation, Eurobonds, and changes in pensions in a context that fosters contestation of European integration and its outputs.